2014
DOI: 10.1002/uog.13437
|View full text |Cite
|
Sign up to set email alerts
|

Use of IOTA simple rules for diagnosis of ovarian cancer: meta‐analysis

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 32 publications
4
80
3
3
Order By: Relevance
“…Therefore, we believe that the simple rules are a user-friendly tool for both experienced and less-experienced examiners. For the masses with conclusive results, the sensitivity in this study was lower than that in Nunes [19] reported in their meta-analysis, while the specificity was higher. This difference may be partly explained by the fact that this study was performed in a tertiary care university-affiliated hospital, which was considered to be the best hospital in Qingdao, and partly because the simple rule diagnosis was conducted by a trainee with little clinical experience.…”
Section: Discussioncontrasting
confidence: 89%
“…Therefore, we believe that the simple rules are a user-friendly tool for both experienced and less-experienced examiners. For the masses with conclusive results, the sensitivity in this study was lower than that in Nunes [19] reported in their meta-analysis, while the specificity was higher. This difference may be partly explained by the fact that this study was performed in a tertiary care university-affiliated hospital, which was considered to be the best hospital in Qingdao, and partly because the simple rule diagnosis was conducted by a trainee with little clinical experience.…”
Section: Discussioncontrasting
confidence: 89%
“…Specificity was similar in both centers. This is in agreement with the conclusion drawn by Nunes et al in their recent metaanalysis, that found out that sensitivity of simple rules were higher in papers with higher malignancy rate [12].…”
Section: Commentssupporting
confidence: 87%
“…Several papers have been reported so far validating these SR, used by expert and non-expert examiners [8][9][10][11]. Nunes et al have recently reported a meta-analysis about the use of IOTA simple rules, which conclude that the simple rules can be used in routine clinical practice being an accurate test [12]. However, data about whether these simple rules perform similarly in different clinical settings according to malignancy rate are still scanty.…”
Section: Introductionmentioning
confidence: 96%
“…Ultrasonography is the first choice imaging for assessing a pelvic mass. The simple IOTA rules have an accuracy of 76-89% for the diagnosis of ovarian cancer [23].…”
Section: Resultsmentioning
confidence: 99%